2004
DOI: 10.1002/chin.200426094
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic Activity of 2‐Methyl‐3,4,5‐triaryl‐1H‐pyrroles in SLM and STZ Models.

Abstract: 9 examples) are synthesized and evaluated for their antihyperglycemic activity in sucrose-loaded (SLM) and/or streptozotocin-induced (STZ) diabetic rat models. Three of them, compounds (IIIa), (IIIb), and (IIId), show significant inhibition activity. -(GOEL*, A.; AGARWAL, N.; SINGH, F. V.; SHARON, A.; TIWARI, P.; DIXIT, M.; PRATAP, R.; SRIVASTAVA, A. K.; MAULIK, P. R.; RAM*, V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
0
21
0
1
Order By: Relevance
“…21,22 In current scenario, the treatment of type 2 diabetes has been revolutionized with the advent of insulin sensitizers like rosiglitazone and pioglitazone that ameliorate insulin resistance and thereby normalize elevated blood glucose levels but are also associated with hepatotoxicity, weight gain, and edema (Table I). 23,24 The alarming situation emphasized the need to discover new antihyperglycemic agents with reduced or no side effect.…”
Section: Development Perspectives and Current Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 In current scenario, the treatment of type 2 diabetes has been revolutionized with the advent of insulin sensitizers like rosiglitazone and pioglitazone that ameliorate insulin resistance and thereby normalize elevated blood glucose levels but are also associated with hepatotoxicity, weight gain, and edema (Table I). 23,24 The alarming situation emphasized the need to discover new antihyperglycemic agents with reduced or no side effect.…”
Section: Development Perspectives and Current Statusmentioning
confidence: 99%
“…Holmes et al at Affymax reported a series of novel sulfonamides containing a single DFMP group as potent inhibitors of PTP 1B. SAR around the scaffold was also investigated, leading to the identification of compounds with IC 50 or K i values in the low nanomolar range (17)(18)(19)(20)(21) (Table VI). These sulfonamide-based inhibitors exhibit 100 and 30 times higher inhibitory activity than the corresponding tertiary amines and carboxamides, respectively.…”
Section: B Phosphorus-containing Phosphotyrosyl Mimeticsmentioning
confidence: 99%
“…Os pirázois apresentaram atividade hipoglicemiante in vivo, provavelmente através da inibição da atividade do canal ATP-K + das membranas das células β-pancreáticas, o que induz a produção de insulina (Cottineau et al, 2002). Os derivados de 1Hpirróis,2-metil-3,4,5-trifenil-substituídos mostraram inibição da hiperglicemia pós-prandial em ratos normais e diminuíram a taxa de glicose no plasma dos ratos com diabetes induzido por estreptozotocina (Goel et al, 2004). As piridinas e purinas que contêm o grupo 2,4tiazolidinodiona apresentaram atividade hipoglicêmica (Kim et al, 2004).…”
Section: G Negri 132unclassified
“…Other natural and novel compounds that were tested and reported for potential antihyperglycemic properties (for instance, [113,[129][130][131][132][133][134][135][136]), mostly without detailed characterization of cellular targets and molecular interactions, are not discussed in this review.…”
Section: Insulin Receptor Agonists/enhancersmentioning
confidence: 99%